Transborder Water Resources of Kirghizia - S. K. Alamanov (Проблемы постсоветского пространства)
The geography of water bodies and water resources of Kyrgyzstan was completely observed. Studied the dynamics of water management in different countries related to the restructuring of the water sector in the new conditions of socio-economic development. Analyzed official and expert opinion about positions on using of transboundary water resources in Central Asia. In the article given recommendation for solving problems of transboundary water sharing. Proposed actions and activities among which the main role should play international legal initiatives.